‘I Can’t Create a Future with a Temporary Permit’: Refugees and Long-Term Temporary Protection in Denmark - Mette Lind Kusk (Nordic Journal of Migration Research, 2023)
Recent asylum and immigration policies in Denmark have made temporary protection and repatriation the explicit, political goals. Individuals who are granted asylum or family reunification inevitably face years of temporary protection during which their right to this protection is frequently reassessed, marking their lives in Denmark with fundamental uncertainties. Based on fieldwork with young adults who have spent their formative years in Denmark and who, after as many as 16 years in the country, still hold temporary permits, this article illuminates the impacts of being subjected to temporary protection long-term. Theoretically, the article makes an original contribution by drawing on recent trends in migration research that emphasize temporal aspects of migration in combination with concepts from the anthropology of conflict and violence. By highlighting the permanence of temporary protection, which makes various forms of uncertainty a starting point for refugees’ actions and choices, the article argues that temporary protection subjects individuals to conditions comparable to long-term conflict and crisis. Further, it shows how strategies of hope and hypervigilant behavior serve as avenues to deal with these conditions. While this makes an orientation toward long-term futures possible, it simultaneously increases precarity in everyday realms in the present.